Best practices in literacy instruction (Guilford Press, 2003)
Now in a revised and updated second edition, this bestselling book guides teachers in providing effective, engaging literacy instruction that meets the challenges of today's legislative mandates. Identified are principles of best practice that reflect cutting-edge scientific research as well as decades of hands-on classroom experience, and that were cited in the International Reading Association's 2002 position paper on evidence-based reading instruction. Leading researchers and practitioners review the latest findings on key areas of instruction and translate the research into easy-to-implement teaching strategies and ideas. Including updated coverage of early literacy, phonics, comprehension, assessment, adolescent literacy, and more, the second edition also features essential new chapters on vocabulary and fluency instruction.